2002
DOI: 10.1191/0961203302lu235oa
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of CD3+CD4-CD8- (double negative) T cells in patients with systemic lupus erythematosus: activation markers

Abstract: Systemic lupus erythematosus (SLE) is characterized by B cell hyperactivity and the production of autoantibodies, some of which (antibodies to dsDNA) are thought to be pathogenic. T helper cells drive the production of autoantibodies and the aim of this study is to characterize phenotypically a subpopulation of T cells (the CD3+ CD4- CD8-, double negative (DN) T cells) previously identified as helping to enhance anti-DNA antibodies in patients with SLE. Data were obtained using FACS staining of DN T cells that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
36
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 30 publications
6
36
0
1
Order By: Relevance
“…In accordance with recent findings [12,13], we hypothesized that humoral and cellular immune mechanisms may be fundamentally involved in the pathogenesis of class IV childhood SLE nephritis.…”
Section: Discussionsupporting
confidence: 70%
“…In accordance with recent findings [12,13], we hypothesized that humoral and cellular immune mechanisms may be fundamentally involved in the pathogenesis of class IV childhood SLE nephritis.…”
Section: Discussionsupporting
confidence: 70%
“…cells are expanded and derive from CD8 ϩ T cells that undergo phenotypic transformation (2)(3)(4)(5), involving the down-regulation of CD8 and the acquisition of a distinct effector phenotype (2,3). Because DN T cells infiltrate tissues, they are believed to be of pathophysiological relevance in SLE (2, 3).…”
Section: Discussionmentioning
confidence: 99%
“…In SLE, several molecular abnormalities contribute to the proinflammatory phenotype and tissue homing of B and T cells. T cell receptor (TCR)-␣␤ ϩ CD3 ϩ CD4 Ϫ CD8 Ϫ "double-negative" (DN) T cells are expanded in the peripheral blood and infiltrate tissues, where they induce immunoglobulin production and secrete proinflammatory cytokines (2)(3)(4)(5). Recently, we demonstrated that human DN T cells derive from CD8…”
Section: Systemic Lupus Erythematosus (Sle)mentioning
confidence: 99%
“…High levels of human lymphocyte antigen DR (HLA-DR) expression on T cells in SLE patients correlated with severity of disease [59].…”
Section: Other Markersmentioning
confidence: 99%